A new visualisation and measurement technology for water continuous multiphase flows. (December 2015) - Wang, Mi; Jia, Jiabin; Faraj, Yousef; Wang, Qiang; Xie, Cheng-gang; Oddie, Gary; Primrose, Ken; Qiu, Changhua
Abstract: This paper reports the performance of a research prototype of a new multiphase flow instrument to non-invasively measure the phase flow rates, with the capability to rapidly image the flow distributions of two- and three-phase (gas and/or oil in water) flows. The research prototype is based on the novel concepts of combining vector Electrical Impedance Tomography (EIT) sensor (for measuring dispersed-phase velocity and fraction) with an electromagnetic flow metre (EMF, for measuring continuous-phase velocity with the EIT input) and a gradiomanometer flow-mixture density metre (FDM), in addition to on-line water conductivity, temperature and absolute pressure measurements. EIT–EMF–FDM data fusion embedded in the research prototype, including online calibration/compensation of conductivity change due to the change of fluids' temperature or ionic concentration, enables the determination of mean concentration, mean velocity and hence the mean flow rate of each individual phase based on the measurement of dispersed-phase distributions and velocity profiles. Results from first flow-loop experiments conducted at Schlumberger Gould Research (SGR) will be described. The performance of the research prototype in flow-rate measurements are evaluated by comparison with the flow-loop references. The results indicate that optimum performance of the research prototype for three-phase flows is confined within the measuring envelope 45–100% Water-in-Liquid Ratio (WLR) and 0–45% Gas Volume Fraction (GVF). Within the scope of this joint research project funded by the UK Engineering & Physical Sciences Research Council (EPSRC), only vertical flows with a conductive continuous liquid phase will be addressed. Graphical abstract: